'Do dead men tell no tales?' The geographic origin of a colonial period Anglican cemetery population in Adelaide, South Australia, determined by isotope analyses. Issue 2 (4th May 2022) - Adams, Christine; Owen, Timothy D.; Pate, F. Donald; Bruce, David; Nielson, Kristine; Klaebe, Robert; Henneberg, Maciej; Moffat, Ian
Abstract: Tooth enamel and dentine samples from 13 individuals buried in the unmarked 'free ground' colonial section of St Mary's Anglican Cemetery in Adelaide were analysed for oxygen and strontium isotopic composition to assist with the determination of their geographic origin. As the life history of these individuals is not well-documented in the historical record, isotopic data provide important information about migration and mobility in a colonial South Australian population. This was supplemented with further analysis of diet from previously published stable isotope data. While the results are somewhat ambiguous, they suggest that of the 13 individuals in this study, one was probably born in Adelaide, eight in Britain/Ireland, three could have been born in either location; one was born elsewhere. This interpretation supplements and supports the results from the analysis of skeletal morphology, microbiomes, and historical records.